LA COMPRENSIÓN DE LA SALUD COMO METACAPACIDAD EN EL PROGRAMA FAMILIA, MUJER E INFANCIA. - Pérez Tamayo, Eliana María; Peñaranda Correa, Fernando (Hacia la Promoción de la Salud)
Objetive: To understand the promotion of human development approach in the Family, Woman and Childhood Program (FAMI by its acronym in Spanish) in the Northeastern zonal service of the Colombian Family Welfare Institute (ICBF by its acronym in Spanish), Medellin (Antioquia) branch, analyzing the contributions that such a promotion can provide to the theory and practice of public health. Materials and Methods: Qualitative study with theoretical support on the human capabilities approach by Martha Nussbaum and of health as metacapability by Sridhar Venkatapuram and methodologically based on ethnographic techniques. In-depth interviews with community mothers, user mothers and professionals of the program were conducted in this research, and participant observation in various community settings was also carried out. Results: The findings are related to a group of seven core capabilities arising from the FAMI program. Conclusion: The seven capacities identified among mothers in the FAMI program interact synergistically to potentiate health as metacapability aimed to achieve decent living.